Analisa Hidrolis Sistem Distribusi Air Bersih di Desa Nogosari Pacitan - Supardi .; Gede Satya; Djoko Sasono (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract. Clean water is basic human need that has an important role in supporting life. In addition to cooking purposes, clean water is also necessary for bathing and other needs. Problems faced by rural communities at Nogosari are particularly trouble getting clean water in the dry season, sources of water used daily is the dray season river with very small debit and tend to dry. Another potential source of water has a distance of approximately three miles from the location. Seeing the problems, the water distribution system is conducted in rural districts Nogosari Ngadirojo Pacitan regency.The analysis is done by calculating the projected population to obtain clean water needs. Then the distribution nedwork analysis using Epanet 2.0 program is conducted with the expectation to serve the needs of clean water for rural communities.Keywords : Clean water distribution, Epanet 2.0